2018
DOI: 10.3989/gya.0230181
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and anticancer efficacy of therapeutic bioactive compounds from fermented olive waste

Abstract: Olive pomace, which is considered as one of the worst agro-industrial wastes in Mediterranean countries was tested for bioactive compounds production through the solid state fermentation of Kluyveromyces marxianus. Because they present potent biological activities, phenolic compounds from both unfermented and fermented pomace were extracted with simultaneous evaluation of their antioxidant and anticancer activities. Conditions for optimum total phenolic recovery with maximum antioxidant activity were optimized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
0
2
1
5
Order By: Relevance
“…Its main properties have been reported in many studies that have highlighted its biological activities. Specifically, their effects on human health are anti-inflammatory, anti-hyperglycemic, hepatoprotective, cardioprotective, antimicrobial and anticancer [ 6 , 7 , 8 ]. Recent studies [ 9 ] suggest that the main biophenols found in Olea europaea L. products and sub-products may be used as a potential source of both antioxidant and anticancer effects, and in particular, in ovarian cancer that is characterized by a high mortality rate among gynecological malignancies worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Its main properties have been reported in many studies that have highlighted its biological activities. Specifically, their effects on human health are anti-inflammatory, anti-hyperglycemic, hepatoprotective, cardioprotective, antimicrobial and anticancer [ 6 , 7 , 8 ]. Recent studies [ 9 ] suggest that the main biophenols found in Olea europaea L. products and sub-products may be used as a potential source of both antioxidant and anticancer effects, and in particular, in ovarian cancer that is characterized by a high mortality rate among gynecological malignancies worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…On one hand, the olive oil industry has to compete with other low-cost vegetable oils, such as sunflower or palm oil. On the other hand, it is required to develop sustainable and environmentally friendly management for the olive mill solid waste (OMSW) generated during extraction [1]. The OMSW results from the two-phase olive oil manufacturing process, being a high-humidity and polluting waste, where the remains of olive fruit are retained.…”
Section: Introductionmentioning
confidence: 99%
“…Além dos compostos fenólicos isolados, os extratos das águas de resíduos (DORW) também exercem atividade antiproliferativa sobre células MDA-MB-231, comparável ao hidroxitirosol e ao 5-fluorouracil (5-FU), demonstrando o potencial dos extratos de águas de resíduos como fonte de compostos fenólicos para aplicações nutracêuticas, como suplementos alimentares, abrindo novas estratégias para a valorização dos resíduos de produtos da oliveira (Ramos et al, 2013). Outros subprodutos da oliveira que vem ganhando destaque são os extratos do bagaço da azeitona não fermentada (UFOP) e fermentada (FOP), que foram avaliados em MCF-7 nas quais os extratos metanólicos de UFOP e FOP exibiram potente atividade antiproliferativa com IC50 de 25,50 ± 2,67 e 23,25 ± 2,43 μg/ml para UFOP e FOP, respectivamente (doxorrubicina IC50: 24,00 ± 2,72 μg/ml), demonstrando que o IC50 de UFOP e FOP foi próximo ao valor do quimioterápico doxorrubicina (Mahmoud et al, 2018).…”
Section: Câncer De Mamaunclassified
“…O efeito antioxidante e anticâncer dos extratos UFOP e FOP foram estudados em um modelo in vitro de câncer de próstata humano pelo ensaio de coloração SulfoRhodamine-B (SRB), o qual apresentou atividade moderada contra as células PC-3, com IC50 de 38,00 ± 5,06 e 32,90 ± 4,62 µg/ml para UFOP e FOP, respectivamente (Mahmoud et al, 2018).…”
Section: Câncer De Próstataunclassified
See 1 more Smart Citation